1991
DOI: 10.1111/j.1365-2621.1991.tb05311.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Inactivation Improves Stability of Self‐Rising Corn Meals

Abstract: Enzymes affecting corn lipids were inactivated by adjusting whole dent corn to 15% moisture and gradually heating it to 91" or 96°C during passage through a two-stage steam-jacketed conveyer, followed by cooling. Heat-processed and untreated products were then milled by a four-break, 96% extraction procedure. Processed and untreated meals were formulated into self-rising meals and stored at 37°C for 6 months. Processed meal formulations were significantly (P < 0.05) more stable during storage than those from u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…2c and d). De Almeida et al (2014) found a decrease in lipase and POD activities of 75.3% and 90.2% respectively when the grains were steamed for 120 s. As POD enzyme is more heat stable than lipase enzyme (Cenkowski, Ames, & Muir, 2006;Bookwalter, Lyle, & Nelsen, 1991) the 90 s of steam time in our study appears enough to inactivate lipolytic enzymes with only slight effect on POD activity. Initially, an increase in PPO activity was observed due to steam treatment, which may be due to inactivation of a PPO inhibitor.…”
Section: Enzymatic Activities In Fresh Whole Wheat Floursupporting
confidence: 48%
“…2c and d). De Almeida et al (2014) found a decrease in lipase and POD activities of 75.3% and 90.2% respectively when the grains were steamed for 120 s. As POD enzyme is more heat stable than lipase enzyme (Cenkowski, Ames, & Muir, 2006;Bookwalter, Lyle, & Nelsen, 1991) the 90 s of steam time in our study appears enough to inactivate lipolytic enzymes with only slight effect on POD activity. Initially, an increase in PPO activity was observed due to steam treatment, which may be due to inactivation of a PPO inhibitor.…”
Section: Enzymatic Activities In Fresh Whole Wheat Floursupporting
confidence: 48%
“…Thermal processing of grains has been shown to be effective in retarding the off flavor generation during subsequent storage. Bookwalter et al () demonstrated that the self‐rising corn meals produced from heat treated corn flour were more stable and had lower fat acidity values (45 mg/100 g KOH) compared to untreated flour (244 mg/100 g KOH). Molteberg et al () observed that heat treatment (10 min autoclaving) of oat flour reduced the levels of FFA and flavors such as bitterness and astringency.…”
Section: Resultsmentioning
confidence: 99%
“…Clean, undamaged grains essentially store longer time, but the tissue disruption during milling process can initiate degradation reactions. The major limitation in the utilization of whole grain flour is its rapid deterioration of quality owing to the enzymatic breakdown of lipids, consequently leading to reduced storage period (Bookwalter, Lyle, & Nelsen, ). The major ways of lipid degradation are by hydrolytic or oxidative reactions or sometimes combination of both.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations